Study of Literary and Non-Literary Forms of Speech in Literature - qizi, Tulyaganova Nargiza Farxod; Batirovna, Yusupova Shoira (International Journal on Integrated Education, 2023)
In our article we are going to analyse a well -known novel. It is clear to all of us that writing a book in a detective field is a bit difficult. The reason is that the work should not be only attractive for readers, but also have to be a logical connection in the work.